Media Pembelajaran Konsep Genetika Menggunakan Drosophila melanogaster Isolat Lokal Dengan Aplikasi Whatsapp Berbasis Kearifan Lokal Budaya Mapalus - Herry Maurits Sumampouw; Mokosuli Yermia Semuel; Dewa Nyoman Oka; Orbanus Naharia; Masje Wurarah (Jurnal Pendidikan Biologi undiksha, 2021)
The COVID-19 pandemic has changed the conventional learning structure. Learning media is a necessity for students in online learning so that learning objectives can be achieved maximally. The subject of genetics is one of the most difficult materials for students, partly because this field of biology is abstract. Research has been carried out that aims to obtain learning media for genetic concepts using the results of laboratory studies of local isolates of fruit flies. Learning media is packaged with a local wisdom approach, namely mapalus culture, and packaged for use in the what's app application. This study applies the research and development method of the ADDIE model (Analysis, Design, Development, Implementation). The test instrument used in this study is the product validity results from material experts and media experts. Research products are uploaded to the youtube channel for easy access and use through the WhatsApp application by students. The results showed that the learning media received an 85% assessment of the feasibility of the material, 83% of the feasibility of the media, and the responses of small group students included in the very good category. Learning media for the concept of genetics uses local isolate fruit flies with the WhatsApp application, based on mapalus culture, which is potential to be used as a medium for learning biology for the subject of genetics.